Clinicopathologic features and surgical treatment prognosis of esophageal carcinosarcoma - Shen, Jiangfeng; Lu, Kaijin; Liu, Fuxing; Chen, Xia; Chen, Quan; Wu, Bingbing; Wang, Hailan; Ge, Pengfei; Han, Guang; Wang, Fei; Zhang, Peng; Yin, Pei; et al. (Frontiers in Oncology, 2024)
Background Carcinosarcoma is a rare esophageal tumor, accounting for approximately 0.27-2.8% of malignant esophageal tumors. This study aims to investigate the clinical pathological characteristics, surgical treatment outcomes, and analysis of prognostic factors in esophageal carcinosarcoma (ECS). Methods Clinical data from sixteen patients diagnosed with esophageal sarcomatoid carcinoma who underwent surgical interventions were retrospectively analyzed. Clinical and pathological features, treatment modalities, and postoperative outcomes were systematically examined. Results Out of the 1261 patients who underwent surgical treatment for esophageal cancer, 16 cases were pathologically confirmed as carcinosarcoma. Among them, two underwent neoadjuvant chemotherapy, six received postoperative chemotherapy. Carcinosarcomas predominantly occurred in the middle (43.75%) and lower (50%) segments of the esophagus. Among the 16 cases, 10 presented as polypoid, 4 as ulcerative, and 2 as medullary types. Microscopic examination revealed coexistence and transitional transitions between sarcomatous and carcinoma components. Pathological staging showed 5 cases in stage T1, 2 in stage T2, and 9 in stage T3, with lymph node metastasis observed in 8 cases (50%). TNM staging revealed 2 cases in stage I, 9 in stage II, and 5 in stage III. The overall 1, 3, and 5-year survival rates were 86.67%, 62.5%, and 57.14%, respectively. Univariate analysis indicated that pathological N staging influenced survival rates, while multivariate analysis demonstrated that pathological N staging was an independent prognostic factor. Conclusions Carcinosarcoma is a rare esophageal tumor, accounting for approximately 0.27-2.8% of malignant esophageal tumors. Histologically, the biphasic pattern is a crucial diagnostic feature, although the carcinomatous component may not always be evident, especially in limited biopsies, leading to potential misclassification as pure sarcoma or squamous cell carcinoma. Despite its large volume and cellular atypia, carcinosarcoma carries a favorable prognosis. Complete surgical resection of the tumor and regional lymph node dissection is the preferred treatment approach for esophageal carcinosarcoma.